Peranan Influencer Marketing Sebagai Strategi Pemasaran Digital 5.0 - As-Syahri, Hidayatullah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Influencer marketing has rapidly evolved as an effective marketing strategy in the digital era, particularly within the context of Digital Marketing 5.0, which integrates advanced technologies such as AI and big data. This research aims to review existing literature on the role of influencer marketing as a digital marketing strategy. Through an analysis of studies from 2018 to 2024, this research explores how influencer marketing influences consumer behavior, enhances brand awareness, and fosters more personal relationships between brands and their audiences. The study also investigates brands' challenges and opportunities in leveraging influencer marketing and how new technologies like AI and data analytics can optimize these strategies. Based on a comprehensive literature review, this research concludes that influencer marketing plays a crucial role in enhancing the effectiveness of digital marketing campaigns. When well-managed and integrated into a comprehensive digital strategy, it can be valuable in achieving broader and sustainable marketing goals in the Digital Marketing 5.0 era .